Preparation method for synthesizing manganese-based Prussian blue positive electrode material with assistance of sodium sulfate
By employing a synergistic co-precipitation process assisted by sodium sulfate synthesis, the stoichiometric ratio of the precursor was precisely controlled, solving the stability problem of manganese-based Prussian blue materials during cycling. This enabled the preparation of efficient and stable manganese-based Prussian blue cathode materials suitable for sodium-ion batteries.
Patent Information
- Application Number
- CN202510622427.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2026-01-23
AI Technical Summary
The stability and cycle performance degradation issues caused by water of crystallization during the cycling process of existing manganese-based Prussian blue cathode materials have not been effectively resolved, affecting their application in sodium-ion batteries.
The preparation method using sodium sulfate-assisted synthesis precisely controls the precursor stoichiometry through a synergistic co-precipitation process, thereby controlling crystal nucleation and growth kinetics, reducing the generation of coordination water and interstitial water, and optimizing lattice structure stability.
It significantly improves the lattice structure stability and electrochemical performance of manganese-based Prussian blue materials, enhances the long-cycle capacity retention and voltage plateau stability of sodium-ion batteries, and has the potential for industrialization due to its ease of operation and environmental friendliness.
Smart Images

Figure CN121377064A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of sodium-ion batteries, in particular to a preparation method of a manganese-based Prussian blue positive electrode material synthesized with the assistance of sodium sulfate. BACKGROUND
[0002] The global energy transformation accelerates the contradiction between supply and demand of lithium resources, and lithium-ion batteries are facing rising raw material costs and supply chain risks. Sodium-ion batteries have become a key alternative technology in the field of large-scale energy storage because of the abundant and widely distributed sodium element. As a core component, Prussian blue analogues have highlighted research value due to their unique advantages: first, the open framework structure can realize the rapid deintercalation of sodium ions, and has high theoretical capacity; second, the three-dimensional ion channel endows it with high working voltage characteristics; third, the raw material cost is significantly lower than that of traditional layered oxide positive electrodes, and the aqueous solution synthesis process also has the advantage of low energy consumption. Compared with other types of positive electrode materials, the Prussian blue system exhibits better industrialization economy and technical adaptability.
[0003] Current research needs to focus on solving the problem of cycle performance decay caused by internal crystallization water in the material, and improving stability through structure optimization and interface regulation. Therefore, a method for preparing Prussian blue analogue positive electrode materials with friendly preparation conditions, simple and efficient, and good stability will provide a better choice for future energy storage scenarios, and has important significance for promoting clean energy transformation. SUMMARY
[0004] The purpose of the application is to provide a preparation method of a manganese-based Prussian blue positive electrode material synthesized with the assistance of sodium sulfate, which has the advantages of manganese-based Prussian blue sodium-ion battery positive electrode materials with friendly preparation conditions, simple and efficient, and good stability, etc. From the perspective of crystal structure control, the influence of coordination water and interstitial water generated during synthesis on the material is effectively reduced, the electrochemical performance of Prussian blue and its analogues as positive electrode materials is fully utilized, and the problem of cycle performance decay caused by internal crystallization water in the material is solved.
[0005] To achieve the above purpose, the application provides the following technical scheme: a preparation method of a manganese-based Prussian blue positive electrode material synthesized with the assistance of sodium sulfate, the manganese-based Prussian blue structure has a general formula of Na x Mn[Fe(CN)6]y·ZH2O, wherein 1 Step one: sodium ferrocyanide, sodium sulfate and sodium citrate are added to deionized water, and then the solution is placed on a magnetic stirrer for stirring to obtain solution A; Step two: manganese salt and ethylenediaminetetraacetic acid tetrasodium are added to deionized water, and the solution is magnetically stirred at room temperature to obtain solution B; Step three: slowly add solution B into solution A under stirring condition using peristaltic pump to obtain solution C; Step four: after stirring, solution C is aged, and the precipitate is separated from solution C by centrifuge, and then washed with deionized water and anhydrous ethanol alternately, and transferred into a vacuum oven for drying to obtain high-stability manganese-based Prussian blue sodium-ion battery positive electrode material.
[0006] Preferably, in step one, the concentration of sodium ferrocyanide is 0.15-0.2 mol / L, the concentration of sodium sulfate is 0.15-0.65 mol / L, and sodium sulfate is used as an auxiliary material for synthesizing manganese-based Prussian blue sodium-ion battery positive electrode material, and the concentration of sodium citrate is 0.3-0.5 mol / L.
[0007] Preferably, in step two, the manganese salt is one of manganese sulfate, manganese acetate and manganese chloride, the concentration of the manganese salt solution is 0.55-0.65 mol / L, and the concentration of the ethylenediaminetetraacetic acid tetrasodium solution is 0.55-0.65 mol / L.
[0008] Preferably, in step three, the flow rate of the peristaltic pump is 1-2 mL / min.
[0009] Preferably, in step four, the aging time is 18-30 h, the rotation speed of the centrifuge is 8500-9500 rpm, the drying temperature is 110-125℃, and the drying time is 12-16 h.
[0010] Preferably, the prepared manganese-based Prussian blue is used as a sodium-ion battery positive electrode material, and the preparation method of the sodium-ion battery is as follows: the manganese-based Prussian blue active material, conductive carbon black and PVDF binder are mixed in a mass ratio of 7:2:1 to prepare a homogeneous slurry with N-methyl pyrrolidone as a dispersion medium, the slurry is uniformly coated on the surface of an aluminum foil current collector by a doctor blade coating method, and then gradient temperature treatment is performed in the range of 80-120℃, and a composite positive electrode sheet is obtained after 12-14 hours of vacuum hot pressing drying. Battery assembly: in a sealed operating environment with an argon gas protective atmosphere, a sodium metal foil is used as a counter electrode, a glass fiber membrane is used as an ion-conducting separator, and after injecting a sodium salt-containing electrolyte, a CR2032 type button cell is packaged; the electrolyte is composed of a sodium salt electrolyte, a carbonate solvent and a functional additive, and the specific preparation method is as follows: sodium hexafluorophosphate is dissolved in a blended solvent system with a volume ratio of EC / DEC of 1:1, and then 2% of fluoroethylene carbonate (FEC) is added as a film-forming optimizer, and finally an electrolyte system with a sodium ion concentration of 1 mol / L is obtained.
[0011] Compared with the prior art, the present application has the following advantages: 1. The manganese-based Prussian blue analogue positive electrode material is prepared by the above method and a synergistic co-precipitation process, the dynamic balance of nucleation and growth kinetics is realized by accurately adjusting the stoichiometric ratio of the precursor, and the formation of crystal vacancy defects is effectively inhibited. Experiments show that the process effectively reduces the content of coordinated water and interstitial water in the material, greatly reduces the probability of side reactions. Based on the defect engineering strategy optimization, the material exhibits excellent lattice structure stability, and maintains a low volume change during the sodium ion extraction process. As a positive electrode of sodium ion battery, the manganese-based Prussian blue analogue electrode material exhibits good capacity retention and voltage platform stability in long cycle test.
[0012] 2. The scheme is based on the stoichiometric ratio control strategy, and a room temperature co-precipitation synthesis path is developed, which has the advantages of simple operation, environmental friendliness and product structure. Through the synergistic control of precursor ratio, the dynamic balance of crystal nucleation-growth is realized under non-high temperature conditions, and the product purity optimization and defect concentration control are simultaneously achieved. The green synthesis process has obvious large-scale production adaptability, and its low energy consumption characteristics coupled with excellent batch stability, providing an efficient preparation scheme for the industrial application of Prussian blue electrode materials. BRIEF DESCRIPTION OF DRAWINGS
[0013] Figure 1 The scanning electron microscope surface morphology diagram of the sample prepared in Example 2 is shown in the figure; Figure 2 The discharge cycle diagram of the sample prepared in Example 1, Example 2 and Example 3 and the sample prepared in the comparative example as an electrode material under a current density of 100 mA / g is shown in the figure; Figure 3 The cycle rate diagram of the sample prepared in Example 2 under different current densities is shown in the figure. DETAILED DESCRIPTION
[0014] Please refer to Figures 1-3 A preparation method of a sodium sulfate-assisted manganese-based Prussian blue positive electrode material, the manganese-based Prussian blue structure prepared has a general formula of Na x Mn[Fe(CN)6]y·ZH2O, wherein 1 Step one: sodium ferrocyanide, sodium sulfate and sodium citrate are added to deionized water, and then the solution is placed on a magnetic stirrer for stirring to obtain solution A; Step two: manganese salt and ethylenediaminetetraacetic acid tetrasodium are added to deionized water, and the solution is magnetically stirred at room temperature to obtain solution B; Step three: solution B is slowly added to solution A under stirring conditions using a peristaltic pump to obtain solution C; Step four: After the solution C is stirred and aged, the precipitate is separated from the solution C by a centrifuge, and then washed with deionized water and anhydrous ethanol alternately, and transferred to a vacuum oven for drying to obtain a high-stability manganese-based Prussian blue sodium-ion battery positive electrode material.
[0015] In step one, the concentration of sodium ferrocyanide is 0.15-0.2 mol / L, the concentration of sodium sulfate is 0.15-0.65 mol / L, and sodium sulfate is used as an auxiliary material for synthesizing the manganese-based Prussian blue sodium-ion battery positive electrode material, and the concentration of sodium citrate is 0.3-0.5 mol / L; In step two, the manganese salt is one of manganese sulfate, manganese acetate, and manganese chloride, and the concentration of the manganese salt solution is 0.55-0.65 mol / L, and the concentration of the ethylenediaminetetraacetic acid tetrasodium solution is 0.55-0.65 mol / L; In step three, the flow rate of the peristaltic pump is 1-2 mL / min; In step four, the aging time is 18-30 h, the centrifuge speed is 8500-9500 rpm, the drying temperature is 110-125℃, and the drying time is 12-16 h.
[0016] The prepared manganese-based Prussian blue is used as a sodium-ion battery positive electrode material, and the preparation method of the sodium-ion battery is as follows: the manganese-based Prussian blue active material, conductive carbon black, and PVDF binder are mixed in a mass ratio of 7:2:1 to prepare a homogeneous slurry with N-methyl pyrrolidone as a dispersion medium, uniformly coated on the surface of an aluminum foil current collector by a doctor blade coating method, and then subjected to gradient temperature rising treatment in the range of 80-120℃. After 12-14 hours of vacuum heat pressing and drying, a composite positive electrode sheet is obtained. Battery assembly: in a sealed operating environment with an argon gas protective atmosphere, a sodium metal foil is used as a counter electrode, a glass fiber membrane is used as an ion-conducting separator, and after injecting a sodium salt-containing electrolyte, a CR2032 type button cell is packaged; the electrolyte is composed of a sodium salt electrolyte, a carbonate solvent, and a functional additive, and the specific preparation method is as follows: sodium hexafluorophosphate is dissolved in a blended solvent system with a volume ratio of EC / DEC of 1:1, and then 2% of fluoroethylene carbonate (FEC) is added as a film-forming optimizer, and finally a sodium ion concentration of 1 mol / L is obtained.
[0017] Example one: Step one: 0.005 mol of sodium ferrocyanide, 0.01 mol of sodium sulfate, and 0.02 mol of sodium citrate are added to 33 mL of deionized water, and then the solution is placed on a magnetic stirrer for stirring to obtain solution A; Step two: 0.01 mol of manganese sulfate and 0.01 mol of ethylenediaminetetraacetic acid tetrasodium are added to 17 mL of deionized water, and then the solution is placed on a magnetic stirrer for stirring to obtain solution B; Step 3: Under stirring conditions, use a peristaltic pump to slowly add solution B to solution A at a flow rate of 1 mL / min to obtain solution C; Step 4: After stirring solution C, let it stand for aging for 24 hours. Then, use a centrifuge at 9000 rpm to separate the precipitate from solution C. Wash the precipitate alternately with deionized water and anhydrous ethanol, and then transfer it to a vacuum oven at 120°C for drying for 12 hours to obtain the manganese-based Prussian blue sodium-ion battery cathode material synthesized with sodium sulfate assistance.
[0018] Depend on Figure 2 As can be seen, after the sample from Example 1 was fabricated into an electrode and assembled into a sodium-ion battery, electrochemical tests were performed, and the test voltage range was 2–3.9 V (vs Na). + / Na), with a current density of 100 mA / g. The initial reversible capacity of the electrode material in Example 1 was 76.3 mAh / g, and the reversible capacity after 100 cycles was 72.8 mAh / g.
[0019] Example 2: Step 1: Add 0.005 mol sodium ferrocyanide, 0.02 mol sodium sulfate, and 0.02 mol sodium citrate to 33 mL of deionized water, and then place the solution on a magnetic stirrer to stir, to obtain solution A; Step 2: Add 0.01 mol manganese sulfate and 0.01 mol tetrasodium ethylenediaminetetraacetate to 17 mL of deionized water, and then place the solution on a magnetic stirrer to stir, to obtain solution B; Step 3: Under stirring conditions, use a peristaltic pump to slowly add solution B to solution A at a flow rate of 1 mL / min to obtain solution C; Step 4: After stirring solution C, let it stand for aging for 24 hours. Then, use a centrifuge at 9000 rpm to separate the precipitate from solution C. Wash the precipitate alternately with deionized water and anhydrous ethanol, and then transfer it to a vacuum oven at 120°C for drying for 12 hours to obtain the manganese-based Prussian blue sodium-ion battery cathode material synthesized with sodium sulfate assistance.
[0020] Depend on Figure 1 As can be seen, the product obtained in Example 2 exhibits monodisperse nanoparticle morphology, and its multi-scale structural advantages are reflected in two aspects: first, the high dispersion effectively constructs a three-dimensional ion transport network, optimizing the sodium ion migration path length to the submicron level; second, the well-ordered particle-electrolyte interface significantly reduces charge transfer impedance. This multi-level structure regulation strategy, through the synergistic effect of shortening the solid-phase mass transfer distance and enhancing interfacial dynamics, enables the electrode material to exhibit faster ion migration dynamics under charge-discharge conditions.
[0021] Depend on Figure 3As can be seen, after the sample from Example 2 was made into an electrode and assembled into a sodium-ion battery, electrochemical tests were performed, and the test voltage range was 2–3.9 V (vs Na). + The electrode material of Example 2 had an initial reversible capacity of 82.8 mAh / g and a reversible capacity of 74.1 mAh / g after 100 cycles, with a capacity retention of 89.5%, demonstrating better electrochemical performance compared to other samples.
[0022] Depend on Figure 3 As can be seen, the electrode material of the sample in Example 2 has good capacity retention under different current densities, exhibits good rate performance, and demonstrates excellent adaptability to the working environment.
[0023] Example 3: Step 1: Add 0.005 mol sodium ferrocyanide, 0.04 mol sodium sulfate, and 0.02 mol sodium citrate to 33 mL of deionized water, and then place the solution on a magnetic stirrer to stir, to obtain solution A; Step 2: Add 0.01 mol manganese sulfate and 0.01 mol tetrasodium ethylenediaminetetraacetate to 17 mL of deionized water, and then place the solution on a magnetic stirrer to stir, to obtain solution B; Step 3: Under stirring conditions, use a peristaltic pump to slowly add solution B to solution A at a flow rate of 1 mL / min to obtain solution C; Step 4: After stirring solution C, let it stand for aging for 24 hours. Then, use a centrifuge at 9000 rpm to separate the precipitate from solution C. Wash the precipitate alternately with deionized water and anhydrous ethanol, and then transfer it to a vacuum oven at 120°C for drying for 12 hours to obtain the manganese-based Prussian blue sodium-ion battery cathode material synthesized with sodium sulfate assistance.
[0024] Depend on Figure 2 As can be seen, after the sample from Example 3 was fabricated into an electrode and assembled into a sodium-ion battery, electrochemical tests were performed, and the test voltage range was 2–3.9 V (vs Na). + The current density was 100 mA / g. The initial reversible capacity of the electrode material in Example 3 was 81.8 mAh / g, but after 100 cycles, the reversible capacity was only 63.5 mAh / g.
[0025] Comparative example: Step 1: Add 0.005 mol sodium ferrocyanide and 0.02 mol sodium citrate to 33 mL of deionized water, then place the solution on a magnetic stirrer and stir to obtain solution A; Step 2: Add 0.01 mol manganese sulfate and 0.01 mol tetrasodium ethylenediaminetetraacetate to 17 mL of deionized water, and then place the solution on a magnetic stirrer to stir, to obtain solution B; Step 3: Under stirring conditions, use a peristaltic pump to slowly add solution B to solution A at a flow rate of 1 mL / min to obtain solution C; Step 4: After stirring solution C, let it stand for aging for 24 hours. Then, use a centrifuge at 9000 rpm to separate the precipitate from solution C. Wash the precipitate alternately with deionized water and anhydrous ethanol, and then transfer it to a vacuum oven at 120°C to dry for 12 hours to obtain manganese-based Prussian blue sodium ion battery cathode material.
[0026] Depend on Figure 2 As can be seen, compared with the sample of Example 2, the initial capacity of the comparative sample was 67.1 mAh / g, and the reversible capacity after 100 cycles was only 59.7 mAh / g, indicating poor capacity performance and cycle stability.
[0027] In summary, this method for preparing manganese-based Prussian blue cathode material with sodium sulfate assistance solves the problem of cycle performance degradation caused by internal crystal water in the material.
Claims
1. A method for preparing manganese-based Prussian blue cathode material with sodium sulfate-assisted synthesis, characterized in that: The prepared manganese-based Prussian blue has the general structural formula Na. x Mn[Fe(CN)6]y·ZH2O, where 1<x≤2, 0.8<y<1, is prepared by following these steps; Step 1: Add sodium ferrocyanide, sodium sulfate, and sodium citrate to deionized water, then place the solution on a magnetic stirrer and stir to obtain solution A; Step 2: Add manganese salt and tetrasodium ethylenediaminetetraacetate to deionized water, and magnetically stir the solution at room temperature to obtain solution B; Step 3: Under stirring conditions, use a peristaltic pump to slowly add solution B to solution A to obtain solution C; Step 4: After stirring solution C, age it. Separate the precipitate from solution C using a centrifuge, then wash it alternately with deionized water and anhydrous ethanol, and transfer it to a vacuum oven for drying to obtain a high-stability manganese-based Prussian blue sodium-ion battery cathode material.
2. The method for preparing a manganese-based Prussian blue cathode material with sodium sulfate assistance according to claim 1, characterized in that: In step one, the concentration of sodium ferrocyanide is 0.15-0.2 mol / L, the concentration of sodium sulfate is 0.15-0.65 mol / L, and sodium sulfate is used as an auxiliary material for synthesizing the positive electrode material of manganese-based Prussian blue sodium ion battery, while the concentration of sodium citrate is 0.3-0.5 mol / L.
3. The method for preparing a manganese-based Prussian blue cathode material with sodium sulfate-assisted synthesis according to claim 1, characterized in that: In step two, the manganese salt is one of manganese sulfate, manganese acetate, and manganese chloride, and the concentration of the manganese salt solution is 0.55-0.65 mol / L, and the concentration of the tetrasodium ethylenediaminetetraacetate solution is 0.55-0.65 mol / L.
4. The method for preparing a manganese-based Prussian blue cathode material assisted by sodium sulfate according to claim 1, characterized in that: In step three, the flow rate of the peristaltic pump is 1-2 mL / min.
5. The method for preparing a manganese-based Prussian blue cathode material with sodium sulfate assistance according to claim 1, characterized in that: In step four, the aging time is 18-30 hours, the centrifuge speed is 8500-9500 rpm, the drying temperature is 110-125℃, and the drying time is 12-16 hours.
6. The method for preparing a manganese-based Prussian blue cathode material with sodium sulfate-assisted synthesis according to claim 1, characterized in that: The prepared manganese-based Prussian blue is used as a positive electrode material for sodium-ion batteries. The preparation method of sodium-ion batteries is as follows: the manganese-based Prussian blue active material is mixed with conductive carbon black and PVDF binder in a mass ratio of 7:2:1, and N-methylpyrrolidone is used as a dispersion medium to prepare a homogeneous slurry. The slurry is uniformly coated on the surface of aluminum foil current collector by a doctor blade coating method, and then subjected to gradient heating treatment in the range of 80-120℃. After vacuum hot pressing and drying for 12-14 hours, a composite positive electrode sheet is obtained. Battery assembly: In a closed operating environment under argon protection, sodium metal foil is used as the counter electrode, glass fiber membrane is used as the ion conduction separator, and sodium salt electrolyte is injected to complete the CR2032 button battery encapsulation. The electrolyte is composed of sodium salt electrolyte, carbonate blend solvent and functional additives. The specific preparation method is as follows: sodium hexafluorophosphate is dissolved in a blend solvent system with an EC / DEC volume ratio of 1:1, and then 2% by mass of fluoroethylene carbonate (FEC) is added as a film-forming optimizer to finally obtain an electrolyte system with a sodium ion concentration of 1 mol / L.